Designing an Instructional Model to Improve Reading Abilities of Technical Documents and Learning Attitudes for Vocational Students in China - Luo, Fei; Chano, Jiraporn; Chen, Hengliang (International Journal of Language Education, 2024)
The purpose of this study is to develop an instructional model to improve the reading abilities of technical documents, and to enhance students’ positive learning attitudes for TVE college students in China. This study developed a teaching model based on the Information Processing Approach, Vygotsky's Scaffolding, and Motivation. This teaching mode has the characteristics and technical attributes of TVE, which can (a) improve the reading ability of TVE college students on technical documentation, and (b) enhance the students' positive learning attitude (enthusiasm). This teaching model includes (1) Principles of the model, (2) Objectives, (3) Syntax, (4) Social system, (5) Principles of reaction, and (6) Support system. Through the application of two classes at Shenzhen Institute Technology in China, it can be seen that three-information input and output activities can be formed in both applications, and there is a progressive relationship between the three activities, and the three activities can fully stimulate students' learning enthusiasm.